Earnings and Firm Value in the Presence of Real Options - Hiemann, Moritz (The Accounting Review, 2020)
ABSTRACT To explain the empirically documented nonlinear, non-monotonic relationship between earnings and firm value, it suffices to assume that firms continually take profit-maximizing decisions in response to newly arriving investment opportunities. The real options embedded in these opportunities create hysteresis effects that lead to the well-known, but so far poorly understood, negative earnings-to-value relation among loss-making firms. Optionality also predicts the future growth component of firm value to be a decreasing function of earnings among highly profitable firms. More generally, the dynamic options model implies an earnings-to-value mapping that can be non-monotonic even over narrow earnings intervals. The commonly used linear earnings-response estimation may, therefore, be a poor approximation even locally. These phenomena arise because optionality makes past and future earnings the product of an unobservable flow of opportunities and decisions whose time dynamics cannot be described by direct linear past-to-future extrapolation.